Pengaruh Evaluasi Kinerja Terhadap Komitmen Organisasional Karyawan - Asep Rudi Hartono; Maya Setiawardani (Jurnal Riset Bisnis dan Investasi, 2017)
This study examines the company's performance appraisal, employee’s organizational commitment and the influence of organizational commitment on employee’s performance appraisal in PT Indonesia Power UBP Suralaya. The dataset encompasses observations using questionnaire (195 respondents). The methods of analysis in this research are classical assumption test, descriptive analysis, correlation, linear regression, and test hypotheses using the SPSS program. Research results show that the performance appraisal is already good, and organizational commitment of employees are already high. There is a strong link between performance appraisal with the organizational commitment of employees. The influence of performance appraisal has a positive effect for 46.6% on the organizational commitment of employees while the rest 53.4% is affected by other factors such as job satisfaction, job characteristics and other factors which are not examined in this study.